2018
DOI: 10.1016/j.immuni.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Loss of NF-κB1 Causes Gastric Cancer with Aberrant Inflammation and Expression of Immune Checkpoint Regulators in a STAT-1-Dependent Manner

Abstract: Polymorphisms in NFKB1 that diminish its expression have been linked to human inflammatory diseases and increased risk for epithelial cancers. The underlying mechanisms are unknown, and the link is perplexing given that NF-kB signaling reportedly typically exerts pro-tumorigenic activity. Here we have shown that NF-kB1 deficiency, even loss of a single allele, resulted in spontaneous invasive gastric cancer (GC) in mice that mirrored the histopathological progression of human intestinal-type gastric adenocarci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 71 publications
5
78
0
Order By: Relevance
“…Our current study also provides molecular mechanisms responsible for the reprogramming of tumor-suppressing neutrophils. The expression of immune checkpoint T cell inhibitory molecule PD-L1 on neutrophils was shown to be under the control of STAT1 (21,22). We observed that Tollip deficiency leads to reduced activation of STAT1 in Tollip -/neutrophils that is consistent with reduced PD-L1 expression.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Our current study also provides molecular mechanisms responsible for the reprogramming of tumor-suppressing neutrophils. The expression of immune checkpoint T cell inhibitory molecule PD-L1 on neutrophils was shown to be under the control of STAT1 (21,22). We observed that Tollip deficiency leads to reduced activation of STAT1 in Tollip -/neutrophils that is consistent with reduced PD-L1 expression.…”
Section: Discussionsupporting
confidence: 52%
“…We next examined the underlying molecular mechanisms responsible for the neutrophil reprogramming due to Tollip deficiency. Previous studies reported that STAT5 and STAT1 are differentially involved in the expression of CD80 and PD-L1, with STAT5 promoting the expression of CD80 (20) and STAT1 promoting the expression of PD-L1 (21,22). Thus, we tested the activation of STAT1 and STAT5 as well as other key signaling molecules in WT and Tollip -/neutrophils.…”
Section: Resultsmentioning
confidence: 98%
“…For instance, CagA + strains of H. pylori elicit more robust inflammation and are associated with a higher incidence of cancer (50,51). Furthermore, polymorphisms in genes encoding the inflammatory mediators IL1B or NFKB1 dramatically increase the risk of gastric cancer in H. pylori-infected individuals (9,52,53), and can even promote cancer development in the absence of infection (6)(7)(8). Here we demonstrate that signaling by endogenous glucocorticoids is required to suppress pathogenic gastric inflammation metaplasia.…”
Section: Adrenal Hormones Are Required To Suppress Spem Developmentmentioning
confidence: 69%
“…Several experimental models have shown that chronic inflammation is sufficient to induce gastric cancer development independent of H. pylori infection. Mice overexpressing the proinflammatory cytokines IL1B or IFNG in parietal cells, or that have dysregulated NFKB activity, exhibit spontaneous gastric inflammation leading to metaplasia and gastric cancer (6)(7)(8). In humans, polymorphisms in the IL1B or NFKB1 genes are linked to gastric cancer development, even in the absence of H. pylori infection (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…One of the main pathways activated in response to infection with pathogenic bacteria is nuclear factor κB (NF-κB) signaling, which has been suggested to play a role in inflammation and carcinogenesis (DiDonato et al, 2012). It comprises three pathways: the canonical, non-canonical and p105 pathway -all of which are important for the response to infections and the induction of inflammatory mediators but may also be relevant for the modulation of the inflammatory response (Banerjee et al, 2014;O'Reilly et al, 2018). Canonical NF-κB signaling can be activated by a variety of effectors, such as LPS or tumor necrosis factor α (TNF-α) (Newton and Dixit, 2012).…”
Section: Introductionmentioning
confidence: 99%